Safety profile of hormonal contraception in premenopause - Męczekalski, Błażej; Czyżyk, Adam; Katulski, Krzysztof; Maciejewska-Jeske, Marzena (Menopause Review/Przegląd Menopauzalny, 2013)
In premenopausal women the fecundity rate is decreased, however it is difficult to indicate when the probability of conception is totally excluded. Because of that, in this population hormonal contraception is often prescribed. The use of combined oral contraception is linked to an increased cardio-vascular risk (venous thromboembolism, myocardial infarction, stroke), breast cancer and a moderately elevated risk of cervical cancer. Additionally, the age is a risk factor for those diseases. On the other hand, combined contraception is related with a decreased risk of developing some neoplasms and may prevent menopausal symptoms and abnormal bleeding. The data concerning bone mineral density are inconsistent. Progestin-only contraception is thought to have a better safety profile, but the data in this respect are rather scant. In the light of existing data, combined hormonal contraception is a safe option in lean, nonsmoking premenopausal women without circulatory or metabolic traits. In obese, smoking women with cardio-vascular disease or diabetes, the hormonal or copper intrauterine device, barrier methods or sterilization seem to be a safe option.